UBE2B promotes ovarian cancer growth via promoting RAD18 mediated ZMYM2 monoubiquitination and stabilization. Issue 4 (1st April 2022) - Zeng, Xi; Zheng, Wen; Sheng, Yuting; Ma, Hongwei
ABSTRACT: Ubiquitin-conjugating enzyme E2 B (UBE2B) can form a heterodimer with ubiquitin E3 ligase RAD18. In this study, we aimed to explore new substrates of the UBE2B/RAD18 complex and their regulatory effects in ovarian cancer. Protein physical interactions were predicted using GeneMANIA. Serial sections of commercial ovarian cancer tissue arrays were used to check the protein expression of UBE2B, RAD18, and ZMYM2. Immunofluorescence staining and co-immunoprecipitation assays were performed to check their location and interactions. Cycloheximide chase assay was applied to explore the influence of UBE2B and RAD18 on ZMYM2 degradation. Xenograft tumor models were constructed to assess the influence of the UBE2B-ZMYM2 axis on in vivo tumor growth. A strong positive correlation between UBE2B and ZMYM2 and a moderate positive correlation between RAD18 and ZMYM2 were observed in 23 ovarian cancer cases. In CAOV4 and OVCAR3 cells, myc-ZMYM2 interacted with UBE2B and RAD18. UBE2B and ZMYM2 could be detected in the samples immunoprecipitated by anti-RAD18. UBE2B overexpression or knockdown did not alter ZMYM2 mRNA expression. UBE2B overexpression increased ZMYM2 monoubiquitination but reduced its polyubiquitination. RAD18 knockdown impaired UBE2B- induced ZMYM2 monoubiquitination. UBE2B overexpression significantly enhanced the stability of ZMYM2 protein, the effect of which was weakened by RAD18 knockdown. UBE2B overexpression significantly enhanced the growth of xenograft tumors derived from CAOV4 cells. ZMYM2 knockdown remarkedly suppressed tumor growth and impaired the growth-promoting effect of UBE2B overexpression. In conclusion, this study revealed a novel regulatory effect of the UBE2B/RAD18 complex on ZMYM2 monoubiquitination and stability in ovarian cancer. Graphic Abstract: uf0001